2020
DOI: 10.1038/s41522-020-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymicrobial periodontal disease triggers a wide radius of effect and unique virome

Abstract: Periodontal disease is a microbially-mediated inflammatory disease of tooth-supporting tissues that leads to bone and tissue loss around teeth. Although bacterially-mediated mechanisms of alveolar bone destruction have been widely studied, the effects of a polymicrobial infection on the periodontal ligament and microbiome/virome have not been well explored. Therefore, the current investigation introduced a new mouse model of periodontal disease to examine the effects of a polymicrobial infection on periodontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 63 publications
4
72
0
1
Order By: Relevance
“…However, only few studies have evaluated the oral viral community [43] , [44] , [45] , [48] , [49] and, thus, more studies are still necessary to evaluate the role of the virome in the oral microbiome.…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 99%
See 1 more Smart Citation
“…However, only few studies have evaluated the oral viral community [43] , [44] , [45] , [48] , [49] and, thus, more studies are still necessary to evaluate the role of the virome in the oral microbiome.…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 99%
“…Recently, our group introduced a new polymicrobial mouse model of periodontal disease in a common mouse strain (BALB/cBy), which revealed a widening of the periodontal ligament space, alveolar bone loss, and an increased host immune response after a polymicrobial infection [49] . This model may be useful for assaying microbial biofilm interactions in vivo .…”
Section: Oral Biofilm Dysbiosis Signatures Of Common Diseasesmentioning
confidence: 99%
“…However, to be most useful, all relevant PHMs and opportunistic infections would need to be considered. This perspective is in accord with the increasing recognition of the importance of polymicrobial infections [24,54,326,327].…”
Section: Testing the Phm Hypothesismentioning
confidence: 53%
“…However, some studies have shown a thinning of the cortical plates, observed as hard lines on radiographs, and the expansion of the PDL in the root apex and interradicular regions (regions far removed from the site of insult) as clinically important evidence of periodontal disease 57,58 . Furthermore, we recently reported that periodontal disease induced by a polymicrobial infection in mice caused PDL expansion beyond the site of bone loss, which was far from the site of initial bacterial infection 59 . In the present study, the number of TRAP‐positive cells increased in areas distant from the ligated site compared to the controls, whereas BAP expression was maintained in the resorption lacunae of the alveolar bone.…”
Section: Discussionmentioning
confidence: 99%